2018
DOI: 10.1103/physrevlett.121.247202
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hydrogen in the Spin-Orbital-Entangled Quantum Liquid Candidate H3LiIr2O6

Abstract: Motivated by recent reports of H3LiIr2O6 as a spin-orbital-entangled quantum liquid, we investigate via a combination of density functional theory and non-perturbative exact diagonalization the microscopic nature of its magnetic interactions. We find that while the interlayer O-H-O bond geometry strongly affects the local magnetic couplings, these bonds are likely to remain symmetrical due to large zero-point fluctuations of the H positions. In this case, the estimated magnetic model lies close to the classica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 61 publications
(64 reference statements)
3
44
0
Order By: Relevance
“…Note: After finalizing this manuscript we became aware of other computational study on H 3 LiIr 2 O 6 using a combination of DFT and non-perturbative ED [44]. The effective magnetic couplings and the trends induced by disorder that are reported in that investigation are consistent with our findings.…”
Section: Introductionsupporting
confidence: 81%
“…Note: After finalizing this manuscript we became aware of other computational study on H 3 LiIr 2 O 6 using a combination of DFT and non-perturbative ED [44]. The effective magnetic couplings and the trends induced by disorder that are reported in that investigation are consistent with our findings.…”
Section: Introductionsupporting
confidence: 81%
“…Theoretical ab initio calculations have also shown for these systems that although the bond-dependent Kitaev interactions are significant, the Heisenberg and other non-Kitaev terms are not negligible. It has been suggested that these systems lie close to the tricritical point between ferromagnetic, zigzag, and incommensurate spiral order resulting in the absence of magnetic order [18]. Calculations further reveal that the interlayer O-H-O geometry as well as lack of hydrogen order also strongly influence the Kitaev and other exchange interactions having strong impact on its magnetic properties [18,19].…”
Section: Introductionmentioning
confidence: 94%
“…However, it is also known that these honeycomb materials cannot fully be understood by the original (pure) Kitaev model 12,13 . While other diagonal or offdiagonal interactions might be important in real materials 14 , the importance of disorder has been ignored in these materials until recently [15][16][17] . Indeed, experiments in A 3 LiIr 2 O 6 (A = H, Ag, etc.)…”
Section: Introductionmentioning
confidence: 99%